First, we'll impose the constraint of existence of square
root;
x>=0
1 +
sqrtx>=0
We'll subtract 1 both
sides:
x - 1 = sqrt[1 +
sqrt(x)]
We'll raise to square both sides, to eliminate the
square root from the right side:
(x-1)^2 = 1 + sqrt
x
We'll expand the square:
x^2
- 2x + 1 = 1 + sqrtx
We'll eliminate like
terms:
x^2 - 2x = sqrt x
We'll
raise to square:
(x^2 - 2x)^2 =
x
[x(x - 2)]^2 - x = 0
We'll
factorize by x:
x[x(x-2)^2 - 1] =
0
x1 = 0
x(x-2)^2 - 1 =
0
We'll expand the square:
x^3
- 4x^2 + 4x - 1 = 0
We'll factorize the middle terms by
-4x:
(x^3 - 1) - 4x(x - 1) =
0
We'll re-write the difference of
cubes;
x^3 - 1 = (x - 1)(x^2 + x +
1)
(x - 1)(x^2 + x + 1) - 4x(x - 1) =
0
We'll factorize by
(x-1):
(x-1)(x^2 + x + 1 - 4x) =
0
x - 1 = 0
x2 =
1
x^2 - 3x + 1 = 0
We'll apply
the quadratic formula:
x3 = [3+sqrt(9 -
4)]/2
x3 = (3 + sqrt5)/2
x4 =
(3 - sqrt5)/2
The solutions of the equation
are: {0 ; (3 - sqrt5)/2 ; 1 ; (3 + sqrt5)/2}.
No comments:
Post a Comment